Mitotic DNA synthesis is caused by transcription-replication conflicts in BRCA2-deficient cells - Groelly, Florian J; Dagg, Rebecca A; Petropoulos, Michalis; Rossetti, Giacomo G; Prasad, Birbal; Panagopoulos, Andreas; Paulsen, Teressa; Karamichali, Angeliki; Jones, Samuel E; Ochs, Fena; Dionellis, Vasilis S; Puig Lombardi, Emilia; et al. (Molecular cell, 2022)
Aberrant replication causes cells lacking BRCA2 to enter mitosis with under-replicated DNA, which activates a repair mechanism known as mitotic DNA synthesis (MiDAS). Here, we identify genome-wide the sites where MiDAS reactions occur when BRCA2 is abrogated. High-resolution profiling revealed that these sites are different from MiDAS at aphidicolin-induced common fragile sites in that they map to genomic regions replicating in the early S-phase, which are close to early-firing replication origins, are highly transcribed, and display R-loop-forming potential. Both transcription inhibition in early S-phase and RNaseH1 overexpression reduced MiDAS in BRCA2-deficient cells, indicating that transcription-replication conflicts (TRCs) and R-loops are the source of MiDAS. Importantly, the MiDAS sites identified in BRCA2-deficient cells also represent hotspots for genomic rearrangements in BRCA2-mutated breast tumors. Thus, our work provides a mechanism for how tumor-predisposing BRCA2 inactivation links transcription-induced DNA damage with mitotic DNA repair to fuel the genomic instability characteristic of cancer cells.